Logic and Workings of Least Squares Method - Cholakov, Nikola (Research Papers, 2007)
Linear statistical models and the method of least squares play a central role in statistical theory and practice. It is examined in this study the application of the least squares method in linear statistical models in diverge areas of statistics – from regression analysis to sample surveys, econometric modeling and forecasting. The emphasis is on the common methodological groundwork of the applications in otherwise diverge subject and problem areas, including the deep relation between the ordinary and the generalized least squares and other statistical approaches and methods. The main directions of analysis are mapped out and the most important procedural points are underlined.